Developing Tourism Along Delicate Multi Ethnicities: The Tales Of Malaysia Truly Asia - Mohamed, Badaruddin (Universiti Sains Malaysia, 2016)

(untitled)
Malaysia is a proud host for three major ethnic groups-the Malays, Chinese and Indians, plus hundred more minority indigenous people, found mainly in the rural areas of states in the Peninsular Malaysia, Sabah and Sarawak. Tourism means different thing to different ethnic groups. Some, especially the Chinese, had been involved in the tourism sector from day one, while others were basically induced at a later stage, into the hotel and tourist transportation and other related industries. The euphoria from the success of intense and offensive tourism drive starting from the early 1990s, has uplifted tourism to be one of Malaysia’s most important sector that can spurred economic growth for the country. Riding on perhaps the most effective slogan—Malaysia, Truly Asia—tagline, Malaysia has been reporting steady growth in term of tourist numbers and the estimated income generated from the sector. New businesses and new regions being promoted and flourished and people have become elated about the prospect of tourism. Tourism has also changed the way the local people look at tourism. Supported by the government, the Malays and Indians are striving to gain a piece of tourism pie from the more dominating and enterprising Chinese. Despite many measures and potentials to increase Malays and Indians participation in the tourism sector, these two ethnic groups would often find themselves at the peripheral of the tourism network. This paper focuses on challenges faced by Malaysia to ensure that the spirit Malaysia-Truly Asia is shared among its major ethnic groups and at the same time, the benefits and participation in the tourism sector are equally enjoyed.